Effects of Classroom Physical Environment on the Academic Achievement Scores of Secondary School Students in Kohat Division, Pakistan - Suleman, Qaiser; Hussain, Dr Ishtiaq (2014)
The purpose of the paper was to examine the effects of classroom physical environment on the academic achievement scores of secondary school students. All the students studying at secondary school level in Kohat Division, Pakistan constituted the population of the study. The study was delimited to the students of class 09 of Govt. High School Khurram (Karak). Forty students from class 09 of the same school were selected as sample through simple random sampling technique. The study was experimental in nature and therefore “Pre-test-Post-test Equivalent Groups Design ” was used. Statistical data was collected through pre-test and post-test technique. Statistical tools i.e., mean, standard deviation and differences of means were calculated for each group. Significance of the difference between the mean scores of the experimental and control groups was tested at 0.05 level of confidence by applying t-test. After analysis, it was concluded that classroom favorable environment has a significant positive effect on the academic achievement scores of secondary school students. The students of experimental group showed better performance as compared to the students of control group. Based on findings, it was recommended that classroom physical environment should be well-organized, equiped and facilitated.
Keywords: BE:LMIC; BE:RELEVANT